3D-FEM Based Methodology for Analysing Contour Milling Processes of Ti Alloys. (2015) - Batista, M.; Morales, A.; Gómez-Parra, A.; Salguero, J.; Puerta, F.J.; Marcos, M.
Abstract: At present, the use of titanium alloys is increasing in a wide range of applications in different industrial sectors, especially in the aerospace industry. Machining is a very important process in this sector. However, aeronautical titanium alloys are classified as materials that are difficult to machine. A very current technique in the research field of machining by material removal is the use of simulations using the Finite Element Method (FEM). These simulations can notably reduce the number of experimental tests and allow obtaining a first approximation of the process without the need for long-lasting and expensive experiments. This paper presents a methodology for the geometrical definition of common contour-mill tools used in the aerospace industry. Through the section of the active cutting area of the tool and using optical measurements, a 3D model of the tool can be produced. Afterwards, the 3D solid model is imported to FEM software, where the study of it is possible for improving the performance of the machining process.